Characterization and comparison of injuries caused by spontaneous versus organized dogfighting - Intarapanich, N.P.; Touroo, R.M.; Rozanski, E.A.; Reisman, R.W.; Intarapanich, P.P.; McCobb, E.C. (Journal of the American Veterinary Medical Association, 2017)
OBJECTIVE To characterize and compare injuries found in dogs involved in spontaneously occurring dogfights with those of dogs used in illegal organized dogfighting. DESIGN Retrospective case-control study. ANIMALS 36 medium-sized dogs evaluated following spontaneous fights with a dog of the same sex and similar weight (medium dog–medium dog [MDMD] fights), 160 small dogs examined following spontaneous fights with a larger dog (big dog–little dog [BDLD] fights), and 62 dogs evaluated after being seized in connection with dogfighting law enforcement raids. PROCEDURES Demographic characteristics and injuries were recorded from medical records. Prevalence of soft tissue injuries in predetermined body surface zones, as well as dental or skeletal injuries, was determined for dogs grouped by involvement in BDLD, MDMD, and organized dogfights. The extent of injuries in each location was scored and compared among groups by 1-factor ANOVA. Patterns of injuries commonly incurred by each group were determined by use of prevalence data. RESULTS Mean extent of injury scores differed significantly among groups for all body surface zones except the eye and periorbital region. Mean scores for dental injuries and rib fractures also differed significantly among groups. Organized fighting dogs more commonly had multiple injuries, particularly of the thoracic limbs, dorsal and lateral aspects of the head and muzzle or oral mucosa, dorsal and lateral aspects of the neck, and ventral neck and thoracic region. CONCLUSIONS AND CLINICAL RELEVANCE To the authors’ knowledge, this was the first study to compare injuries incurred during spontaneous and organized dogfighting. Establishing evidence-based patterns of injury will help clinicians identify dogs injured by organized dogfighting and aid in the prosecution of this crime. © 2017, American Veterinary Medical Association. All rights reserved.
Keywords: Animals; Article; Athletic Injuries; Behavior, Animal; Bites and Stings; Case-Control Studies; Dogs; Female; Injury Severity Score; Male; Retrospective Studies; Violence; age; animal; animal behavior; bite wound; bites and stings; body surface; case control study; comparative study; dept.mat; dog; dog bite; dog breed; female; fighting; injuries; injury; injury scale; male; nonhuman; pathophysiology; prevalence; retrospective study; rib fracture; scoring system; soft tissue injury; sport injury; tooth injury; veterinary; violence

Factors affecting the acquisition of energy-efficient durable goods - Kuusela, H.; Spence, M.T. (Greener Marketing: A Global Perspective on Greening Marketing Practice, 2017)
Keywords: dept.mat

Predicting students' graduation outcomes through support vector machines - Pang, Yulei; Judd, Nicolas; O'Brien, Joseph; Ben-Avie, Michael (2017 IEEE Frontiers in Education Conference (FIE), 2017)
Low graduation rate is a significant and growing problem in U.S. higher education systems. Although previous studies have demonstrated the usefulness of building statistical models for predicting students' graduation outcomes, advanced machine learning models promise to improve the effectiveness of these models, and hone in on the “difference that makes a difference” not only on the group level, but also on the level of the individual student. In this paper we propose an ensemble support vector machines based model for predicting students' graduation. Up to about 100 features, including a set of psychological-educational factors, were employed to construct the predicting model. We evaluated the proposed model using data taken from a state university's longitudinal, cohort data sets from the incoming classes of students from 2011-2012 (n=350). The experimental results demonstrated the effectiveness of the model, with considerable accuracy, precision, and recall. This paper presents the results of analysis that were conducted in order to gauge the predictive capability of a machine learning algorithm to predict on-time graduation that took into consideration students' learning and development.
Keywords: Artificial intelligence; Education computing; Forecasting; Graduation outcome; Graduation rates; Group level; Higher education; Higher education system; Kernel; Learning algorithms; Learning systems; Machine learning; Machine learning algorithms; Machine learning models; Measurement; Predicting models; Predictive capabilities; Predictive models; Seminars; Students; Support vector machine; Support vector machines; advanced machine learning models; dept.mat; ensemble support vector machines; further education; graduation outcome; higher education; higher education systems; learning (artificial intelligence); low graduation rate; machine learning; on-time graduation; psychological-educational factors; statistical analysis; statistical models; support vector machine; support vector machines

Sally modules and reduction numbers of ideals - Ghezzi, L.; Goto, S.; Hong, J.; Vasconcelos, W. V. (Nagoya Mathematical Journal, 2017)
We study the relationship between the reduction number of a primary ideal of a local ring relative to one of its minimal reductions and the multiplicity of the corresponding Sally module. This paper is focused on three goals: (i) to develop a change of rings technique for the Sally module of an ideal to allow extension of results from Cohen–Macaulay rings to more general rings; (ii) to use the fiber of the Sally modules of almost complete intersection ideals to connect its structure to the Cohen–Macaulayness of the special fiber ring; (iii) to extend some of the results of (i) to two-dimensional Buchsbaum rings. Along the way, we provide an explicit realization of the S2S_{2} -fication of arbitrary Buchsbaum rings.
Keywords: 13D40; 13H15; Primary 13H10; Secondary 13A30; dept.mat

Minimizing positive integer sequences without duplicate substrings - Carrigan, Braxton; Kagey, Peter; O’Brien, Joseph (Geombinatorics, 2017)
Keywords: dept.mat; ⛔ No DOI found

Invariants of Cohen–Macaulay rings associated to their canonical ideals - Ghezzi, Laura; Goto, Shiro; Hong, Jooyoun; Vasconcelos, Wolmer V (Journal of Algebra, 2017)
The purpose of this paper is to introduce new invariants of Cohen–Macaulay local rings. Our focus is the class of Cohen–Macaulay local rings that admit a canonical ideal. Attached to each such ring R with a canonical ideal C, there are integers–the type of R, the reduction number of C–that provide valuable metrics to express the deviation of R from being a Gorenstein ring. We enlarge this list with other integers–the roots of R and several canonical degrees. The latter are multiplicity based functions of the Rees algebra of C. © 2017 Elsevier Inc.
Keywords: Analytic spread; Canonical degree; Cohen–Macaulay type; Reduction number; Roots; dept.mat; peer-reviewed

Masters of mathematics: The problems they solved, why these are important, and what you should know about them - Nowlan, Robert A. (Masters of Mathematics: The Problems They Solved, Why These Are Important, and What You Should Know about Them, 2017)
The original title for this work was “Mathematical Literacy, What Is It and Why You Need it”. The current title reflects that there can be no real learning in any subject, unless questions of who, what, when, where, why and how are raised in the minds of the learners. The book is not a mathematical text, and there are no assigned exercises or exams. It is written for reasonably intelligent and curious individuals, both those who value mathematics, aware of its many important applications and others who have been inappropriately exposed to mathematics, leading to indifference to the subject, fear and even loathing. These feelings are all consequences of meaningless presentations, drill, rote learning and being lost as the purpose of what is being studied. Mathematics education needs a radical reform. There is more than one way to accomplish this. Here the author presents his approach of wrapping mathematical ideas in a story. To learn one first must develop an interest in a problem and the curiosity to find how masters of mathematics have solved them. What is necessary to be mathematically literate? It’s not about solving algebraic equations or even making a geometric proof. These are valuable skills but not evidence of literacy. We often seek answers but learning to ask pertinent questions is the road to mathematical literacy. Here is the good news: new mathematical ideas have a way of finding applications. This is known as “the unreasonable effectiveness of mathematics.”
Keywords: dept.mat

Fault localizations through feature selections - Pang, Yulei; Xue, Xiaozhen; Namin, Akbar Siami (International Journal of Software Engineering and Knowledge Engineering, 2017)
We introduce a novel application of feature ranking methods to the fault localization problem. We envision the problem of localizing causes of failures as instances of ranking program's elements where elements are conceptualized as features. In this paper, we define features as program's statements. However, in its fine-grained definition, the idea of program's features can refer to any traits of programs. This paper proposes feature ranking-based algorithms. The algorithms analyze execution traces of both passing and failing test cases, and extract the bug signatures from the failing test cases. The proposed procedure extracts possible combinations of program's elements when executed together from bug signatures. The feature ranking-based algorithms then order statements according to the suspiciousness of the combinations. When viewed as sequences, the combination of program's elements produced and traced in bug signatures can be utilized to reason about the common longest subsequence. The common longest subsequence of bug signatures represents the common statements executed by all failing test cases and thus provides a means for identifying statements that contain possible faults. Our evaluation indicates that the proposed feature-based fault localization outperforms existing fault localization ranking schemes. © 2017 World Scientific Publishing Company.
Keywords: Artificial intelligence; Computer debugging; Execution trace; Fault localization; Feature ranking; Feature-based; Fine grained; Learning systems; Novel applications; Software engineering; Test case; debugging; dept.mat; feature ranking methods; machine learning

Predicting vulnerable software components through deep neural network - Pang, Yulei; Xue, Xiaozhen; Wang, Huaying (ACM, 2017)
Vulnerabilities need to be detected and removed from software. Although previous studies demonstrated the usefulness of employing prediction techniques in deciding about vulnerabilities of software components, the improvement of effectiveness of these prediction techniques is still a grand challenging research question. This paper employed a technique based on a deep neural network with rectifier linear units trained with stochastic gradient descent method and batch normalization, for predicting vulnerable software components. The features are defined as continuous sequences of tokens in source code files. Besides, a statistical feature selection algorithm is then employed to reduce the feature and search space. We evaluated the proposed technique based on some Java Android applications, and the results demonstrated that the proposed technique could predict vulnerable classes, i.e., software components, with high precision, accuracy and recall.
Keywords: Android; Android (operating system); Android applications; Application programs; Communication channels (information theory); Computer software; Continuous sequences; Deep learning; Deep neural networks; Education; Forecasting; Java programming language; Network security; Neural network; Neural networks; Prediction techniques; Research questions; Software component; Statistical features; Stochastic gradient descent method; Stochastic systems; Vulnerability prediction; deep learning; dept.mat; neural network; vulnerability prediction

On the exact distribution of Wald’s SPRT for the negative exponential model - Starvaggi, Patrick; Khan, M K (Sequential Analysis, 2017)
In this article, we derive the joint Laplace transform of the sequential probability ratio test (SPRT) and the resulting stopped random walk process for the negative exponential model. The Laplace transform is derived by solving a related difference equation. This technique is novel because it only takes advantage of the Markov structure and does not rely on the typical martingale methods used for deriving the Laplace transform of other SPRTs. The joint Laplace transform provides the joint distribution of the SPRT and the associated stopped process, which is a new result. Even the marginal distributions were hitherto unknown. © 2017 Taylor & Francis.
Keywords: Difference equations; Exact distribution; Joint distributions; Laplace transform; Laplace transforms; Marginal distribution; Negative exponential model; Random walk process; SPRT; Sequential probability ratio test; dept.mat; sequential probability ratio test; variance